Analisis Kinerja Ruas Jalan Kembang Seri – Simpang Kandis Di Kota Bengkulu (Studi Kasus Jalan Air Sebakul – Jalan Betungan Kota Bengkulu) - Anggraini, Wulan Puspa (Fakultas Pertanian, 2025)
This study analyzes the performance of the Kembang Seri–Simpang Kandis road corridor, focusing on the Air Sebakul–Betungan segment in Bengkulu City, with the aim of evaluating level of service, degree of saturation, delay, and queue length, and of providing improvement recommendations. Data were collected through field surveys on Monday and Saturday during peak traffic periods (morning 06:00–08:00, midday 11:30–14:00, and evening 15:30–17:00 WIB). Primary data included geometric conditions, traffic composition and volume, travel speed, and roadside obstructions; secondary data were obtained from relevant agencies and documents using the Indonesian Road Capacity Guidelines (PKJI, 2017) as reference. Traffic counts were carried out manually at 15-minute intervals; speeds were measured on a 100 m segment; and roadside obstruction observations were recorded on a 200 m segment. The analysis found that the degree of saturation (DS) on this segment ranged from 0.2291 to 0.4639, placing the roadway at Level of Service B — traffic flow is relatively stable though operating speeds are beginning to be constrained by traffic conditions. Peak-period delay and queue lengths reached maximums at certain times (e.g., maximum delay at Simpang Betungan was 3.5366; maximum queues reached approximately 18–19 vehicles at some locations), but overall the corridor has not experienced severe congestion. Recommendations include infrastructure improvements (drainage, traffic signs, pavement markings, zebra crossings), mitigation of roadside obstructions, and roadway upgrades, as well as further studies on traffic growth for long-term planning. These findings are expected to support efforts to improve safety and traffic flow on the Air Sebakul–Betungan corridor.